2021
DOI: 10.1001/jamasurg.2021.3752
|View full text |Cite
|
Sign up to set email alerts
|

The Reporting of Race and Ethnicity in Surgery Literature

Abstract: nequities affecting underserved racial and ethnic groups continue to be identified across the spectrum of medical research. [1][2][3][4] From the disproportionate number of Black and Hispanic persons who have been hospitalized or died because of COVID-19 in 2020 [5][6][7][8] to discrimination against Asian American persons 9 and the comparatively poor perioperative outcomes even among low-risk racial and ethnic minority patients, 10,11 attentiveness to race and ethnicity has illuminated inequities and disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…19 However, whether or not the journal states they follow guidance or not, this has no impact on the relevance of these data and the importance of reporting them. Additionally, Maduka et al 20 found no difference between journals stating they follow ICMJE recommendations, and those that do not, in the frequency of reporting race and ethnicity in a sample of surgical research publications in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, whether or not the journal states they follow guidance or not, this has no impact on the relevance of these data and the importance of reporting them. Additionally, Maduka et al 20 found no difference between journals stating they follow ICMJE recommendations, and those that do not, in the frequency of reporting race and ethnicity in a sample of surgical research publications in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…During the final review of articles that met inclusion criteria, not all studies reported demographics for their participants, and for those that did, the selection of reporting categories such as "other" were not clearly defined. This is a pervasive issue despite guidelines by the International Committee of Medical Journal Editors and NIH, which defines the standards for the classification of federal data on race and ethnicity [51][52][53][54][55][56]. The editors of the Journal of the American Medical Association recently published "Updated Guidance on the Reporting of Race and Ethnicity in Medical and Science Journals" in response to ongoing issues with reporting, with specific recommendations on the correct use of terms such as sex and gender, and that authors should "define how they determined race or ethnicity and justify their relevance."…”
Section: Discussionmentioning
confidence: 99%
“…The use of ethnoracial categories in medical and health sciences has been the subject of numerous studies that have focused on three main groups of questions: how researchers report on ethnoracial categories in their publications (Ma et al 2007;Zhang and Finkelstein 2019;Maduka et al 2021), on explanations/hypotheses for the use of ethnoracial categories in certain studies (Lee 2009;Sankar et al 2007;Friedman and Lee 2013;Duello et al 2021), and on how scientists conceptualise these categories (Lin and Kelsey, 2000;Huddart et al 2019;Popejoy et al 2020;Popejoy 2021). In the majority of such studies, researchers have adopted two methods to answer the above questions: broadly understood systematic reviews of the literature (e.g., content analysis) of published articles etc., or interviews and surveys carried out in a given community (e.g., geneticists).…”
Section: Methodsmentioning
confidence: 99%